Effect of the application of low shear rates on the crystallization kinetics of PLA. Issue 6 (23rd July 2020) - Volpe, Valentina; Foglia, Fabiana; Pantani, Roberto
Abstract: Flow‐induced crystallization can effectively increase the crystallinity content in poly(lactic acid) parts, and this can be extremely significant since an increase of crystallinity for this material dramatically enhances many properties among which the heat resistance. This work analyzes nucleation and growth rate of spherulites formed during crystallization process of PLA at different temperatures and shear rates. The application of a shear flow results in an enhancement of the nucleation phenomena, with the formation of a new population of nuclei, and an improvement of the crystals growth already at low values of shear rates. Furthermore, it is possible to find a dependence of the equilibrium melting temperature upon the Weissenberg number. Abstract : This work investigates the shear‐induced crystallization of poly(lactic acid) in the spherulitic regime. The application of a shear flow results in an enhancement of the nucleation phenomenon, predominantly in form of point‐like nuclei. The crystal growth rate also increases by the application of a shear flow. Equations for the dependence of nucleation and growth rates on molecular stretch are proposed.